The Influence of Product Quality, Brand Image, and Price Perception on Alfamart's Cooking Oil Purchasing Decision in The Ciracas Area of East Jakarta - Destiani, Anidya; Karyatun, Subur; Digdowiseiso , Kumba (CV ODIS, 2023)
This study aims to determine the influence of product quality, brand image, and price perception on the purchase decision of Alfamart cooking oil in the Ciracas area of East Jakarta. The sample in this study was 100 respondents who made purchasing decisions in the Alfamart Ciracas area, East Jakarta. This study used primary data with a data collection method through questionnaires distributed to 100 respondents. Data analysis techniques using inferential analysis with multiple linear regression and using the Statistical Product and Service Solution (SPSS) program version 23.0. The t-test results show that product quality variables have a positive and significant effect on purchasing decisions, brand image variables have a positive and significant effect on purchasing decisions, and price perception variables have a positive and significant effect on purchasing decisions. Thus it can be concluded that product quality, brand image, and price perception influence purchasing decisions.